2018
DOI: 10.26508/lsa.201700016
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin-mediated translational control is essential for neural cell fate specification

Abstract: Chd5 loss links the up-regulation of ribosomal genes to enhanced translation, causing the untimely production of a master transcription factor that unleashes stem cells and alters cell fate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Our studies recapitulated this observation in GFAP expression during infection and in the long‐term survivors, consistent with sustained neuroinflammation. In NSCs, nestin expression increases during a shift from quiescence to activation (Hwang et al, 2018), suggesting that NSCs in the infected brain may be mobilized to replace lost NSCs or neurons. Even though nestin + cells decreased, we did not detect differences in total nestin expression in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies recapitulated this observation in GFAP expression during infection and in the long‐term survivors, consistent with sustained neuroinflammation. In NSCs, nestin expression increases during a shift from quiescence to activation (Hwang et al, 2018), suggesting that NSCs in the infected brain may be mobilized to replace lost NSCs or neurons. Even though nestin + cells decreased, we did not detect differences in total nestin expression in the brain tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Upon Chd5 depletion, NSCs differentiation was directed toward the astrocytic rather than the neuronal lineage. Boosting of astrocyte differentiation was due to translation disruption of Mash1, a main pro-neural TF that is essential during early differentiation (Hwang et al, 2018 ). These results suggest a strong Chd5 involvement in the cell fate decision in both cortical and hippocampal NSC niches at an early stage of differentiation.…”
Section: Profiling Of Enscs In the Physiological Environmentmentioning
confidence: 99%
“…NSCs and neural progenitors coexist in the embryonic as well as neonatal and adult stages, hence unveiling the mechanism of differentiation since early stages might bring an enormous insight into the global characterization of neurogenesis 10.3389/fncel.2023.1125785 (Codega et al, 2014). A study assessing global gene expression by RNA-seq has shown the role of the chromatin remodelers Chd5 at an early stage of development (Hwang et al, 2018). Chd5, expressed in the post-mitotic neurons, in the neural progenitors of E14.5 rat cortical region, and hippocampal progenitor cells, plays a critical role during neurogenesis (Egan et al, 2013;Vestin and Mills, 2013;Nitarska et al, 2016).…”
Section: Prenatal Development: Focus On Corticogenesismentioning
confidence: 99%
“…neuronal differentiation. However, emerging studies have established the importance of post-transcriptional mechanisms in neuronal differentiation (Kraushar et al, 2014(Kraushar et al, , 2015Blair et al, 2017;Sugiyama et al, 2017;Hwang et al, 2018;Zahr et al, 2018;Mohammad et al, 2019;Tahmasebi et al, 2019). Multiple miRNAs have been shown to regulate distinct aspects of neuronal differentiation (Stappert et al, 2015).…”
Section: Neurogenesis and Differentiationmentioning
confidence: 99%